Influence of the nozzle geometry on in-nozzle cavitation investigated in real-size glass nozzles with shadowgraphy and LIF - Conrad, Chris; Bornschlegel, Sebastian; Durst, Alexander; Jordan, Dominik; Wensing, Michael (ICLASS 2018 - 14th International Conference on Liquid Atomization and Spray Systems, 2020)
The cavitation phenomena inside the nozzle of Gasoline direct injection (GDI) systems directly influence the break-up, formation and propagation of the spray. Especially the process of atomization is strongly driven by the cavitation inside the nozzle. Thus, GDI injectors produce similar droplet sizes in comparison to diesel injectors but with a fraction of the injection pressure. With the help of fused silica glass nozzles, made by selective laser etching, the cavitation phenomena can be visualized inside a realistic geometry. In this study, a binary mixture of n-decane and toluene is used in order to match the refractive index of the nozzle body. Three nozzle geometries with different conicity are investigated with a double shutter shadowgraphy/laser induced fluorescence (LIF) setup in order to compare the results for the two different techniques for the same event. It is shown, that the cavitation phenomena have structural depth when illuminated with the LIF technique while the shadowgraphy images show dark pixels when cavitation is present. In addition, the in-nozzle flow is investigated at flash boiling conditions. It is shown, that a convergent nozzle suppresses sheet cavitation in comparison to a cylindrical or divergent nozzle. All three geometries exhibit highly stochastic string cavitation. Overall, the real-size three dimensional glass nozzles were very well applicable to study the in-nozzle flow and cavitation phenomena with optical measurement techniques.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Cavitation; Flash boiling; GDI; Internal flow; LIF; Selective laser etching; Shadowgraphy; Transparent nozzle